Church and State and the Marital Rights of Old Believers in Latvia: From Illegality to Secularization - Grizāne, Maija (Religions, 2023)
The paper analyses state religious policy in different historical periods and its impact on the development of religious doctrines about marriage within the Old Believer community of Latvia. Based on published and unpublished historical sources, legislative acts, periodicals, and data from existing Old Believer parishes, it is clear that state policy concerning religious minorities greatly influenced the development of the Old Believer community. Old Believer marriages were not recognized by the Russian Orthodox Church until 1874 when the first possibility of obtaining legal marital status was introduced as registering families in police register books. The Old Believers of Latvia, who originally belonged to the Fedoseevcy denomination and denied any family life as such, registered their families quite rarely. However, during the first decades of the 20th century, the Fedoseevcy of Latvia adopted the teaching and marriage ceremonies of the Pomorians. By the interwar period, Old Believer marriages were legalized by both the community and the state. Soviet secularization further facilitated the development of secular marriage unions with followers of other confessions. In the present day, Old Believer religious marriages are legalized in Latvia, though the number of them has decreased as Old Believers are most likely to choose civil marriage registrations.